Elites’ Manipulation and Stakeholders’ Trust in Niger Delta Development: Evidence from a Cross-sectional Survey - Idama Maxwell; Victor Jike Teddy; Ngozi Sandra Ikenyei (PERSPEKTIF, 2025)
This study examined the influence of elite manipulation of the levy system on stakeholders’ engagement in development initiatives in Nigeria’s Niger Delta. Several social research studies have basically addressed issues like oil theft, oil exploration, environmental challenges caused by oil spillage, ethnic conflict, and political neglect. This study differs in perspective as it undertakes an extensive review of the sociological aspects of the community levy system and stakeholder management, involvement, and roles in developmental concerns that affect the region. The objective was to determine how elite interference in the allocation and distribution of community levies affects trust and participation among key stakeholders, including local communities, oil firms, and government agencies. Based on the Elite Theory, which posits that power structures often manipulate resources for private gain, the study employed a quantitative research approach using a cross-sectional survey design. A total of 400 participants were purposively and randomly selected from the Niger Delta communities. Data were collected using a structured questionnaire designed to capture respondents’ perceptions of levy management, elite influence, and stakeholder engagement. Descriptive statistics and the Pearson Product-Moment Correlation were employed to analyze the data and identify relationships among the variables. The findings revealed a significant negative correlation between elite manipulation of community levies and stakeholders’ active participation in local development efforts. It was observed that elite control over levy disbursement erodes community trust and discourages collaborative engagement in development planning and implementation. The study recommended that the Nigerian government and international development partners strengthen accountability and transparency mechanisms in community levy management. Furthermore, it advocated for inclusive governance frameworks that empower local stakeholders, enhance participatory decision-making, and curtail elite dominance in the management of developmental resources. These measures would promote equitable resource utilization and foster sustainable development in the Niger Delta region.